2018
DOI: 10.1007/s11906-018-0889-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Mitochondrial Health to Treat Hypertension

Abstract: Purpose of the Review: This review summarizes literature pertaining to the dawning field of therapeutic targeting of mitochondria in hypertension, and discusses the potential of these interventions to ameliorate hypertension-induced organ damage. Recent Findings: In recent years, mitochondrial dysfunction has been reported as an important contributor to the pathogenesis of hypertension-related renal, cardiac, and vascular disease. This in turn prompted development of novel mitochondria-targeted compounds, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 70 publications
1
18
1
Order By: Relevance
“…It is widely accepted that in AKI and/or chronic kidney disease (CKD) such as DN, mitochondrial biogenesis is significantly affected, and thus could be one of the major reasons for renal tissue damage (Hall and Schuh, 2016;Bhargava and Schnellmann, 2017;Duann and Lin, 2017;Eirin et al, 2018). Surprisingly, little is known about mitochondrial function and biogenesis in SS hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that in AKI and/or chronic kidney disease (CKD) such as DN, mitochondrial biogenesis is significantly affected, and thus could be one of the major reasons for renal tissue damage (Hall and Schuh, 2016;Bhargava and Schnellmann, 2017;Duann and Lin, 2017;Eirin et al, 2018). Surprisingly, little is known about mitochondrial function and biogenesis in SS hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS production is recognized to accelerate HF progression (Wrigley et al, 2011). Thus, a current focus in the treatment of hypertension is identifying treatment modalities that improve mitochondrial health (Eirin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Critically, network-based drug repurposing has recently identified several candidates, such as irbesartan, paroxetine, sirolimus, melatonin and quinacrine, amongst others [ 180 ]. It has been suggested that angiotensin receptor blockers (ARBs) are mitochondrially protective [ 181 ], while anti-depressants, such as paroxetine, can inhibit mitochondrial function [ 182 ]. Sirolimus, or rapamycin, is actually one of the best studied calorie restriction mimetics as it modulates mammalian target of rapamycin (mTOR); it is anti-inflammatory and modulates mitochondrial function, and could play a key role in mitohormesis [ 183 ].…”
Section: Mitochondrial Function and Therapeutic Strategymentioning
confidence: 99%